In Situ Study of Cave 98 Murals on Dunhuang Grottoes Using Portable Laser-Induced Breakdown Spectroscopy - Yin, Yaopeng; Yu, Zongren; Sun, Duixiong; Shan, Zhongwei; Cui, Qiang; Zhang, Yiming; Feng, Yaqi; Shui, Biwen; Wang, Zhuo; Yin, Zhiyuan; Chai, Bolong; Zhang, Wenyuan; et al. (Frontiers in Physics, 2022)
The investigation of painted layers on murals at Cave 98 from Dunhuang Grottoes was carried out in-situ using portable laser-induced breakdown spectroscopy (LIBS) for the first time. The ablation effect of laser pulses on mural surface was evaluated under fixed experimental parameters, and the results showed that the influence of laser ablation on ancient murals was acceptable. Then the pigments used in the red, green and blue layers were indicated with the LIBS spectral data of corresponding color coupled with a classifiable model of pigments based on the Principal Component Analysis (PCA) method. Finally, the depth profiling of the multilayers structure composed with overlapped painted layers was determined based on the pigment size information of the superficial green layer and the relationship of laser shots and ablation depth, and the thickness of the superficial green layer was analyzed quantitatively, which fits well with the result of the cross-sectional analysis. Therefore, this work can shed light on the great potential for ancient mural applications in LIBS.